Contributions of family social structure to the development of ultrasociality in humans. (2016) - Nephew, Benjamin C.; Pittet, Florent
Abstract: The evolution of ultrasociality in humans may have involved the evolutionarily significant mechanisms that govern family social structure in many animal species. Adverse effects of ultrasociality in humans may be mediated by maladaptive effects of modern civilization on family groups, as many of the effects on both families and societies are especially severe in dense populations made possible by agriculture.